(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A study was conducted to isolate and characterize Lactobacilli from the gastrointestinal (GI) tract of broiler chickens in different markets along with evaluation of probiotic ability and antibiotic sensitivity of Lactobacillus isolates during the period of July, 2014 to December, 2014. The caecum and cloacal contents of 100 broiler chickens from different markets were collected and cultured on Man Rogosa and Sharp (MRS) broth and agar. Lactobacilli were isolated and characterized by using phenotypic (cell morphology, Gram’s staining, physiological and biochemical tests which are specific for Lactobacillus genus) and genotypic methods (PCR and RAPD). The identified Lactobacilli species were screened for probiotic properties by in vitro tests like acid tolerance and bile tolerance. Total eighty two isolates were identified as Lactobacillus based on morphological, physiological and biochemical tests which are specific for Lactobacillus genus. All of the Lactobacillus isolates were further identified at species level as Lactobacillus acidophilus, Lactobacillus crispatus, Lactobacillus galinarum and other unclassified Lactobacillus species based on sugar fermentation tests. The prevalence of Lactobacillus crispatus, Lactobacillus acidophilus and Lactobacillus gallinarum species found in the chickens were 21.95%, 18.29% and 17.07% respectively. A total of 10 Lactobacillus isolates were amplified by using 16S rRNA gene-based universal primers. Furthermore, out of 10 Lactobacillus isolates 4 molecular patterns were detected and 6 Lactobacillus isolates were clonal by randomly amplified ploymorphic DNA (RAPD) method in this study. Out of 15 Lactobacillus isolates, 10 isolates demonstrated probiotic ability as determined by bile tolerance test and acid tolerance test. Moreover, the results of antibiotic sensitivity showed that all of the isolates tested were sensitive to tetracycline and gentamicin. However, most of the isolates tested were resistant to ampicillin and cefradine. Potential probiotic bacterial strains from poultry sources were identified as well as characterized in this study. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 54-65